A Study of the Relationships among Consumer Acceptance, Oxidation Chemical Indicators, and Sensory Attributes in High-Oleic and Normal Peanuts - Nepote, Valeria (2008)
The purpose of this study was to determine the relationships between overall acceptance, chemical indicators, and sensory attributes in roasted peanuts harvested from high-oleic peanut genotypes produced in Argentina. Oleic/linoleic ratio (O/L), peroxide value, p-anisidine value, conjugated dienes, consumer acceptance, and descriptive analysis were performed on roasted peanuts prepared using 16 genotypes of normal and high-oleic peanuts. Principal component and cluster analysis were performed on the chemical and sensory data from peanut genotypes. Acceptance was positively associated with O/L, crunchiness, sweetness, roasted peanutty flavor, and hardness. Acceptability was negatively associated with cardboard, oxidized, and sour flavors. The high-oleic genotypes, 4896-11-C, and 9399-10 showed high consumer acceptance with 7 or “like moderately” in a hedonic scale of 9 points. Some high-oleic peanut lines, such as 9399-10, could be used to replace normal peanuts without affecting consumer acceptance of peanut products processed from them and more stability due to the high-oleic condition.